Correlation between markers of renal tubular injury and proteinuria in patients with diabetic kidney disease - Pu Yan; Ning Zhang; Tong-xia Li; Shi-wei Liu (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the correlation between markers of tubular injury, 24 h urine protein quantification (24 hUTP) and albumin creatinine ratio (ACR) in patients with diabetic kidney disease (DKD) and explore the relationship between tubular and glomerular injuries to provide guidance for clinical management of DKD. Methods From November 1, 2019 to December 31, 118 proteinuric patients with a definite diagnosis of DKD at outpatient clinic and ward were recruited. And 24 hUTP, ACR, blood creatinine, urinary N-acety1-β-D-glucosaminidase, alpha 1 microglobulin, retinol-binding protein and kidney injury molecule-1 were measured and estimated glomerular filtration rate (eGFR) calculated by the CKD-EPI formula. Linear correlation analysis was utilized for examining the correlation between markers of proximal tubular injury, tubular reabsorption function and 24 hUTP and ACR. Results 24 hUTP at (0.5-3.5) g/24 h, urinary N-acety1-β-D-glucosaminidase, kidney injury molecule-1, alpha 1 microglobulin, retinol-binding protein were correlated linearly with 24 hUTP. The correlation coefficients (adjusted R2) were 0.192, 0.079, 0.054 and 0.040 respectively. Proximal renal tubular injury markers had the highest correlation with 24 hUTP. Urinary N-acety1-β-D-glucosaminidase, kidney injury molecule-1, alpha 1 microglobulin and retinol-binding protein were correlated linearly with ACR. The correlation coefficients (adjusted R2) were 0.367, 0.058, 0.077 and 0.076 respectively with the best correlation between proximal tubular injury markers and ACR. Conclusions In DKD patients, renal tubular injury markers are correlated linearly with 24 hUTP and ACR. Proximal tubular injury markers have the best correlations with 24 hUTP and ACR. Renal tubular injury is correlated closely with the progression of DKD.